Exchange Rate Effect on Stock Returns in the East European Emerging Markets – A Quantile Regression Approach - Živkov, Dejan; Njegić, Jovan; Markelić, Jelisaveta (Industrija, 2014)
This paper investigates relationship between returns of stock prices and exchange rate changes in four East European emerging markets (Serbia, Poland, Hungary and Czech Republic) using weekly data from January 2003 to June 2013. Two theories explain the connection in the economic literature – flow-oriented and portfolio-balance models, without a finite and conclusive answer on which one is predominant. Considering our relatively large sample period which also includes world crisis outbreak, the used empirical data have been compromised by structural breaks and heterogeneous unconditional distribution. To avoid parameter bias and wrong conclusions, authors used four auto-regressive distributed lag ADL(2,2) models assessed with quantile regression method, robust to non-normality problems. The results indicate that relationship between these variables is in accordance with portfolio-balance models in three out of four analyzed countries.
Keywords: East European countries; Quantile regression; Stock; Exchange rate